IMPRESSION MANAGEMENT STRATEGIES AND ORGANISATIONAL CITIZENSHIP BEHAVIOURS: THE NIGERIAN EXPERIENCE (American Journal of Pedagogical and Educational Research, 2022)
The study examined the correlation between Impression Management Strategies (IMS) and Organizational Citizenship Behaviors (OCB). The sample encompassed 180 randomly selected employees from twelve (12) deposit money banks purposefully chosen in the Niger Delta Region of Nigeria. A quasi-experimental research layout was employed, and data was gathered via a cross-sectional survey. The Spearman Rank Correlation Coefficient using the Statistical Package for Social Sciences (SPSS) Version 25 was deployed for data analysis. The outcomes unveiled a robust positive and statistically significant relationship between IMS and OCB. Concretely, the facets of IMS, including ingratiation, exemplification, and self-promotion, were identified to possess a robust positive and statistically significant relationship with the measures of OCB. Conversely, supplication exhibited a positive but weak and significant relationship with the measures of OCB, while intimidation showcased a negative or inverse relationship with OCB. Predicated on these findings, the study concludes that IMS exerts a significant influence in enhancing OCB in the Nigerian banking industry, with ingratiation, exemplification, and self-promotion exerting a more potent influence than supplication. Moreover, the study concludes that workplace intimidation obstructs OCB. The theoretical and managerial implications of these findings were also discussed.